Kuantitas Mikrob Tanah pada Lahan Jagung dengan Aplikasi Ekstrak Alga - Nur Azizah Amaliah; Nurul Anisa; Norna Norna; Muhammad Habil Ahmad; Fitratul Insaniah Rusli; Hilda Karim; Andi Asmawati Azis; Muhammad Junda; Oslan Jumadi (Institut Pertanian Bogor, 2022)
Organic fertilizers contain complete nutrients needed by plants, such as humic acid and fulvic acid, that can promote plant growth and increase the population of beneficial microbes in the soil. Algae can be an organic fertilizer in extract preparations that can increase plant growth and improve soil composition. The calculated number of microbes from the soil on corn land with the application of algae extracts affects the population of soil microbes both by standard plate count (SPC) and most probable number (MPN) methods. The total number of bacteria by SPC in the control soil was 3.1 × 105 CFU/g, while the total fungus was only 1.7 × 104 CFU/g upon applying 5% algae extract. The most microalgae by MPN in the control ground was estimated to be 2.6 × 104 cells/g. Therefore, the application of algae extract affects the number of soil microbes on corn land compared to control soil. The algae extract reduces the number of bacteria and algae but increases the number of fungi on cornfields. Keywords: algae extracts, cornfields, soil microbes